Sociocultural traits and language attitudes of Chinese Foochow and Hokkien in Malaysia - Ting, Su Hie; Puah, Yan Yann (John Benjamins Publishing Company, 2015)
This study examined the effect of age, gender and socio-economic status on attitudes of Malaysians of Chinese descent towards their Chinese dialect and Mandarin, the standard Chinese language. A survey of 300 Chinese (150 Foochow and 150 Hokkien) living in Kuching, Sarawak was conducted. Their Chinese dialect is valued as an ethnic marker but does not derive its importance from numerical dominance or status of ingroup members. The Foochow and Hokkien participants are significantly different in their attitudes on the importance of their Chinese dialect and Mandarin, and their pride in using these languages but are similar in doubting the instrumental value of their Chinese dialect and Mandarin, feeling embarrassed for not speaking the Chinese languages, and valuing their Chinese dialect as an ethnic marker. Factor analyses identified four and six factors which explained 75.85% and 77.32% of the variance for the Foochow and Hokkien participants' attitudes respectively. The Foochow participants have more homogenous language attitudes than the Hokkien participants. Gender did not have a significant main effect on the language attitudes of both groups but age significantly influenced the Hokkien participants' attitudes. Socio-economic status has significant main and interaction effects on attitudes of both the Foochow and Hokkien participants.